Content Marketing : Sinergi Copywriting Dan Marketing Ads Design Dalam Meningkatkan Efektivitas Pemasaran Digital - Prisilia Putirulan; Lshaday Lamanaga; Miracle Tumbelaka; Natasya J Kalumata; Raymundus Rambing (CV. ITTC INDONESIA, 2025)
Content marketing is a marketing strategy that focuses on creating quality content to attract and retain audiences. In practice, copywriting and marketing ads design are the two main elements that complement each other to create effective and engaging marketing messages. This article discusses the role of copywriting as the art of writing persuasive messages and ad design as a visual element that reinforces these messages in content marketing. The research method uses literature study and content analysis to examine the synergy between copywriting and ad design in improving the effectiveness of digital marketing. The results show that collaboration between copywriting and ad design can increase consumer engagement and conversion. Suggestions are given for companies to optimally integrate these two aspects in their marketing strategies.